Technology and application of environmental and engineering geophysics : selected papers of the 7th International Conference on Environmental and Engineering Geophysics, ICEEG-Beijing 2016 - Di, Qingyun; Xue, Guoqiang; Xia, Jianghai (Springer, 2017)
This book focuses on essential theories, methods and techniques in the field of environmental and engineering geophysics that can contribute to resource detection and environmental protection. Geophysics has been playing an important role in exploring the earth, locating vital resources and promoting the development of society. This book covers a range of topics including the exploration of modern resources, such as ore deposits, coal mines, shale gas and geothermal power, and the monitoring of geological disasters, including the rock-soil body, ground deformation, mines, specific rock-soil engineering disasters, desertification of land and environmental abnormalities. This book not only offers a valuable resource for geophysical researchers; it also demonstrates how geophysics theories and methods can be practically implemented to protect our environment and promote the development of human society.
Keywords: Geophysics -- Congresses.; elektronické knihy; electronic books